Annealing effects on conductivity and optical properties of the PAni layer in ITO/PAni/PPV+DBS/Al polymer light-emitting diodes - Poças, L. C.; Travain, S. A.; Duarte, J. L.; Silva, R. A.; Giacometti, José A; Marletta, Alexandre (IOP Publishing, 2007)
In this work we present the electrical and optical characterization of polymer light-emitting diodes (PLEDs) using indium-tin oxide (ITO), polyaniline (PAni), poly(p-phenylene vinylene) (PPV) +dodecylbenzenesulfonate (DBS) and aluminum (Al). To minimize the conversion temperature and reduce the structural defects of PPV layers, we introduced the counter-ion DBS in the PPV precursor polymer. The best PLED electrical properties were achieved at the PPV conversion temperature of 150 °C. Under this condition, the ITO/PAni/PPV+DBS/Al PLED operating voltage decreases to less than a third of the value obtained with the conventional structure ITO/PPV/Al. In addition, the electrical conductivity increases and the thermal degradation decreases in the PAni layer. The line shape of the PPV electroluminescence spectrum shows no influence of the PAni layer at relatively low electrical field (12MVm-1). © IOP Publishing Ltd.